2016
DOI: 10.3892/mmr.2016.5387
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of the promoter region of the human frizzled 9 gene in acute myeloid leukemia

Abstract: The FZD9 gene is located at chromosome 7q11.23, and has been indicated to be a tumor suppressor gene. The present study examined the involvement of FZD9 promoter methylation in the downregulation of FZD9 expression in leukemia cells. The expression of the FZD9 gene was absent in various leukemic cell lines, while it was restored following treatment with DNA demethylating agent 5‑aza‑2'‑deoxycytidine. Bisulfite sequencing analysis of the FZD9 promoter region showed that it was partially methylated in cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Additionally, FZD9 has an essential role in osteoblast differentiation for bone formation and pre-B cell development [127]. FZD9 has been studied in multiple cancers including NSCLC, astrocytoma, osteosarcoma, AML, and hepatocellular carcinoma (HCC) [96][97][98][99]127]. FZD9 interacts with several WNT ligands including WNT2, WNT5a, and WNT3a depending on the tumor; these interactions promote EMT and invasiveness.…”
Section: Frizzledmentioning
confidence: 99%
“…Additionally, FZD9 has an essential role in osteoblast differentiation for bone formation and pre-B cell development [127]. FZD9 has been studied in multiple cancers including NSCLC, astrocytoma, osteosarcoma, AML, and hepatocellular carcinoma (HCC) [96][97][98][99]127]. FZD9 interacts with several WNT ligands including WNT2, WNT5a, and WNT3a depending on the tumor; these interactions promote EMT and invasiveness.…”
Section: Frizzledmentioning
confidence: 99%
“…However, FZD9 was downregulated in acute myeloid leukemia due to the promoter methylation, suggesting it may also function as a tumor suppressor [ 73 ]. It has been reported that the direct interaction of WNT7a ligand and its receptor FZD9 repressed cell growth and promoted cell differentiation in NSCLC, indicating an antitumor effect of WNT7a and FZD9 in human cancers [ 74 , 75 ].…”
Section: Biological Functions and Mechanismmentioning
confidence: 99%
“…These observations are consistent with a loss of HSPCs during development. Furthermore, disruption of FZD9 expression has been linked to hematological malignancies, highlighting its importance in human hematopoietic cells as well (Jiang et al, 2009;Martin-Subero et al, 2009;Zhang et al, 2016). For instance, FZD9 was identified as one of 6 genes most frequently hypermethylated in hematological neoplasms (Martin-Subero et al, 2009).…”
Section: Egfr and Fzd9b Are Required For The Wnt9a Signal In Vitro Anmentioning
confidence: 99%